Peningkatan Pengetahuan Melalui Edukasi dalam Mengatasi Ketidaknyamanan Selama Masa Kehamilan - Arpen, Ratih Septiana; Silvia, Elwitri; Tyas, Dina Ayuning (Journal of Humanity Dedication, 2024)
Changes in the system in the mother's body during pregnancy will cause discomfort during pregnancy. Discomfort is a feeling that is unpleasant or unpleasant for the physical and mental condition of pregnant women. Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). The target for reducing the maternal mortality rate (MMR) and infant mortality rate (IMR) in Indonesia by 2024 is: MMR: 183 per 100,000 live births. From the initial survey at the service location, namely Posyandu, Lamo Village Hall, Baru Padusunan, Pariaman City, there were 9 people. which come. held on Saturday 14 December 2024. This Community Service Activity aims to increase the knowledge of pregnant women by providing education regarding efforts to overcome discomfort. The method of this activity is through direct counseling to pregnant women. This activity is a means to educate pregnant women who are previously gathered and given counseling on how to reduce it. The results of this community service activity showed an increase in knowledge. The implication of this activity is to provide knowledge and understanding of pregnant women by recognizing physiological/natural discomfort so that pregnant women can overcome their own discomfort at home without having to go to a health facility, so that it does not endanger the health of the mother or fetus.